'Unpleasant' but 'helpful': Immigration detention and urban entanglements in New Jersey, USA. (August 2022) - Conlon, Deirdre; Hiemstra, Nancy
As a reflection of changing geographies of US migration control, when Essex County, New Jersey's local government adopted a new immigration detention contract with the federal government, an elected official noted: 'This is a very unpleasant way of getting revenue…But it's going to be helpful.' Despite politically liberal leanings as well as active and expanding resistance to a persistently conservative immigration enforcement agenda from the national level, New Jersey has been a leading provider of detention in the United States, with numerous counties benefiting significantly from immigration crackdowns. This article examines local debates in three New Jersey municipalities alongside public records data that detail financial relationships central to immigration detention operations, to argue that the ensuing relationships intersect and intertwine in ways that make detention economies a critical facet of municipal development. Further, following a 2021 paper by Lauren Martin, we argue that attention to the array of entities that are linked through detention economies demonstrates the usefulness of understanding the migration 'industry' as an assemblage. Using a site-specific investigative focus we trace myriad entities' involvement in immigration detention and reliance on income from Immigration and Customs Enforcement. We detail how these multifarious actors, sometimes with opposing views on detention and distinct rationalities, converge in ways that contribute to the further entrenchment of detention in municipal areas. Through this focused case study, our analysis advances a critical migration industries approach and details how detention economies are 'assembled' and entangled with urban areas.